Comparative Assessment on the Use of Videogrammetry and Photogrammetry for Rapid and Low-Cost Three-Dimensional Modeling - Nuha, Muhammad Ulin; Pramudya, Alif Farhan; Laia, Bonifasius Efraim; Husain, Rainaldy; Setiaji, Danang; Isnaini, Een Lujainatul; Perdana, Redho Surya; Atmojo, Aulia Try; Jatmiko, Retnadi Heru (Indonesian Journal of Geography, 2024)
The current activities in photogrammetry technology such as the permission to apply non-metric cameras, development of Structure from Motion (SfM), and potential usage of videogrammetry are part of the answers to the need for low-cost camera-based mapping. Therefore, this study aimed to test and compare the accuracy of photogrammetry and videogrammetry methods for three-dimensional (3D) modeling obtained using a non-metric camera with SfM processing. Terrestrial Laser Scanner (TLS) was used to obtain comparative data and the results showed a degradation of photo resolution in videogrammetry method, causing a reduction in the number of point clouds produced compared to photogrammetry. Moreover, the point cloud test showed that the surface variation results for both methods were identical to 3D modeling with a higher point density recorded in photogrammetry and the relative distance was different by 0.125 meters. The average difference in point cloud between photogrammetry and TLS was 0.062 meters while videogrammetry and TLS had 0.106 meters. The absolute test produced an RMSE value of 0.022 meters for photogrammetry and 0.032 meters for videogrammetry at a 95% confidence interval, indicating the two methods produced similar data quality. The results led to the conclusion that videogrammetry had satisfactory values and could be used as an alternative in 3D modeling but was not considered better than photogrammetry. Received: 2023-08-13 Revised: 2024-05-27   Accepted: 2024-09-20 Published: 2024-10-10